Reversal of charge selectivity in transmembrane protein pores by using noncovalent molecular adapters - Gu, Li-Qun (The National Academy of Sciences, 2000)
In this study, the charge selectivity of staphylococcal α-hemolysin (αHL), a bacterial pore-forming toxin, is manipulated by using cyclodextrins as noncovalent molecular adapters. Anion-selective versions of αHL, including the wild-type pore and various mutants, become more anion selective when β-cyclodextrin (βCD) is lodged within the channel lumen. By contrast, the negatively charged adapter, hepta-6-sulfato-β-cyclodextrin (s(7)βCD), produces cation selectivity. The cyclodextrin adapters have similar effects when placed in cation-selective mutant αHL pores. Most probably, hydrated Cl(−) ions partition into the central cavity of βCD more readily than K(+) ions, whereas s(7)βCD introduces a charged ring near the midpoint of the channel lumen and confers cation selectivity through electrostatic interactions. The molecular adapters generate permeability ratios (P(K(+))/P(Cl(−))) over a 200-fold range and should be useful in the de novo design of membrane channels both for basic studies of ion permeation and for applications in biotechnology.